Una nuova prospettiva sul delirio: storia, origine e comprensibilità. Introduzione - Fargnoli, Domenico (Il sogno della farfalla, 2020)
What is delusion? Throughout the history of psychiatry many theories and hypotheses have attempted to explain the origin of delusional ideas. One of the theories that are still accepted nowadays recognizes a similarity between the structure of delusions and dream. Should this theory be considered true or is it possible to offer a new interpretation to this psychopathological symptom? Through these questions the author introduces a monographic issue on the topic of delusion and its comprehensibility.